Equity and justice in global warming policy - Snorre Kverndokk; Adam Rose (Fondazione Eni Enrico Mattei (FEEM), 2008)
Many countries are implementing or at least considering policies to counter increasingly certain negative impacts from climate change. An increasing amount of research has been devoted to the analysis of the costs of climate change and its mitigation, as well as to the design of policies, such as the international Kyoto Protocol, post-Kyoto negotiations, regional initiatives, and unilateral actions. Although most studies on climate change policies in economics have considered efficiency aspects, there is a growing literature on equity and justice. Climate change policy has important dimensions of distributive justice, both within and across generations, but in this paper we survey only studies on the intragenerational aspect, i.e., within a generation. We cover several domains including the international, regional, national, sectoral and inter-personal, and examine aspects such as the distribution of burdens from climate change, climate change policy negotiations in general, implementation of climate agreements using tradable emission permits, and the uncertainty of alternatives to emission reductions.
Keywords: D62; D63; H23; H41; Q00; 330; Economics of Climate Change; Intragenerational Equity; Distributive Justice